Love of God, others, and self and their association with satisfaction with life and mental health for Christians - Jauncey, Tim (Journal of spirituality in mental health, 2018)
This study explored whether the Christian themes of love of God, love of others, and love of self were associated with improved well-being. An online questionnaire was completed by 323 Christians. A structural equation model was developed to explain the relationships between church attendance, love of God, love of others, love of self, presence of meaning, satisfaction with life, depression, anxiety, and physical health. Key findings were that church attendance was beneficial only when mediated by love of God, and that love of God and others improved satisfaction with life only when mediated by meaning in life.